2012
DOI: 10.1002/ajh.23179
|View full text |Cite
|
Sign up to set email alerts
|

Blood component support in acquired coagulopathic conditions: Is there a method to the madness?

Abstract: Acquired coagulopathies are often detected by laboratory investigation in clinical practice. There is a poor correlation between mild to moderate abnormalities of laboratory test and bleeding tendency. Patients who are bleeding due to coagulopathy are often managed with various blood components including plasma, platelets, and cryoprecipitate. However, prophylactic transfusion of these products in a nonbleeding patient to correct mild to moderate abnormality of a coagulation test especially preprocedure is not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 85 publications
1
8
0
Order By: Relevance
“…Patients with microvascular bleeding, or who are at risk of bleeding due to percutaneous procedures, platelets are transfused to achieve a platelet count ≥50,000/microL, and cryoprecipitate transfusion to maintain fibrinogen levels ≥200 mg/dL. [19,20] Ho AM et al [21] (2007) concluded that " the high prevalence of deranged haemostatic measurements after hepatectomy peak on day 2, because of the complex haemostatic changes related to both the cancer and the surgery and it could not be determined whether these changes were associated with an increased risk of epidural hematoma". Another study by Stamenkovic DM et al [22] (2011) noted that "there is no single reported case of epidural hematoma as a consequence of epidural catheter insertion or removal after elective hepatectomy".…”
Section: Discussion:-mentioning
confidence: 99%
“…Patients with microvascular bleeding, or who are at risk of bleeding due to percutaneous procedures, platelets are transfused to achieve a platelet count ≥50,000/microL, and cryoprecipitate transfusion to maintain fibrinogen levels ≥200 mg/dL. [19,20] Ho AM et al [21] (2007) concluded that " the high prevalence of deranged haemostatic measurements after hepatectomy peak on day 2, because of the complex haemostatic changes related to both the cancer and the surgery and it could not be determined whether these changes were associated with an increased risk of epidural hematoma". Another study by Stamenkovic DM et al [22] (2011) noted that "there is no single reported case of epidural hematoma as a consequence of epidural catheter insertion or removal after elective hepatectomy".…”
Section: Discussion:-mentioning
confidence: 99%
“…In severe bleeding FFP transfusion is often recommended but has to be assessed critically regarding its risks and benefits [39,40]. Moreover, transfusion-related acute lung injury, immunomodulation, increased nosocomial infection rates, and last but not least delay of therapy due to the thawing process have to be considered for the use of FFP [42]. Therefore, intravenous fluid restriction rather than prophylactic administration of large volumes of FFP is recommended in patients with gastrointestinal bleeding or undergoing major liver surgery [41].…”
Section: Bleeding Management In Liver Dysfunction and Liver Transplanmentioning
confidence: 99%
“…Because underlying DIC prolongs APTT, adjusting heparin-based anticoagulants in patients with DIC often requires an anti-Xa assay. 15,16 However, low dose heparin has also been used successfully to control ongoing DIC (not due to heparininduced thrombocytopenia) by regulating thrombin. 16,17 Chronic Liver Disease…”
Section: Managementmentioning
confidence: 99%
“…Furthermore, increasing plasma volume and colloidal mass in patients with elevated portal and central venous pressures may further worsen bleeding. 16 The American Association for the Study of Liver Diseases recently advised against the use of plasma to correct PT/INR before liver biopsy. 30,31 Preprocedure plasma therapy (10 to 15 mL/kg) should be reserved for patients with significantly abnormal coagulation values.…”
Section: Managementmentioning
confidence: 99%